Management of Darul Kutub prayer room in improving religious jurisprudence understanding for students at Anwarul Huda Islamic boarding school in Malang - Widodo, Wahyudi (Sean Institute, 2024)
Mosque or musholla is a place of worship for Muslims. In modern times, prayer rooms and mosques are increasingly multiplying and easier to find, resulting in many places where mosques and prayer rooms are renovated to look magnificent and beautiful. Handling this is not a problem if the splendor is also accompanied by many activities in it so that development and activities run well, including one of them at Musholla Darul Kutub. The research method used is qualitative type. The results obtained include: 1) Musholah Management: there are 4 Planning, organizing, mobilizing and supervising. Where in the management is carried out gradually so that the purpose of Musholla for students, especially in the field of religious fiqh is well achieved: 2) The efforts of the Darul Kutub Musholla Management in increasing the understanding of Religious Fiqh, there are several good activities carried out by the musholla management and also cooperation with the head of the pesantren. These activities include: the existence of a library at Musholla Darul Kutub with all kinds of various religious books including contemporary fiqh, the existence of batsul masail activities carried out by the musholla management in collaboration with mutakhorijin students and alumni ustadz related to religious fiqh, and the existence of daily routine religious activities including congregational prayers, and reciting the yellow book from all aspects of the field including fiqh.